Metode Pemahaman Hadis-Hadis Tentang Hakikat TÃ¢â€™Ã»n Studi Kitab Badzl al-MÃ¢â€™Ã»n FÃ® Fadhl al- TÃ¢â€™Ã»n - Siti Hajar (UIN Siber Syekh Nurjati Cirebon, 2022)
Badzl al-MÃ¢â€™Ã»n FÃ® Fadhl al- TÃ¢â€™Ã»n is a thematic hadith book that comprehensively discusses annual hadiths with various perspectives including historical, medical and jurisprudential perspectives. This diversity of perspectives departs from Ibn Hajar's understanding of the hadiths about the meaning of ta'un and its characteristics. This article aims to reveal Ibn Hajar's method when understanding hadiths that talk about the meaning of ta'un and its characteristics. To analyze the data, the researcher use the inductive method, namely by taking an inventory of the products of Ibn Hajar's understanding of the hadiths about the meaning of ta'un and other hadiths related to ta'un, then conclude what methods were used by Ibn Hajar with textual and contextual perspectives. The results of this study are that Ibn Hajar's method of understanding the hadiths about the meaning of ta'un is carried out through two approaches, namely the intratextual and intertextual approaches. In the intratextual approach, he uses the sharh and al-jam' wa al-tawfi>q methods to conclude the history of the beginning of the taâ€™un. through an intertextual approach, he uses linguistic, scientific, historical and asbab al-wuru>d methods. Through an intertextual approach, he draws conclusions regarding the differences between years and epidemics, as well as the main causes of taâ€™un and their characteristics.